Estudio De Los Factores Formativos Intrínsecos Y Extrínsecos Que Influyen En La Conducta De Los Estudiantes De La Unidad Educativa San Carlos De La Parroquia San Carlos, Cantón Quevedo. - Buste Saltos, Walter Eduardo (2014)
The Present Study San Carlos Parish Held It Is On The Premises Of The Educational Unit San Carlos, Quevedo Canton, Province Of Los Ríos, In Order To Evaluate The Influence Of Intrinsic And Extrinsic Factors In The Conduct Of The Students Of The Institution, For The Purpose Of Research And Outreach Of The Objective, Were Identified And Inquired The Causes Of These Factors To Determine Its Effects On The Behavior Of The Learners. To Collect, Interpret And Analyze Primary And Secondary, Information Relating To The Variables Of The Object Of Study, We Used The Types, Methods, Techniques And Instruments For Scientific Research, Methodological Tools Which Allowed Reason And Infer The Quantitative Data And Turn Set A Percentage Value (Statistically) To 286 Students, 20 Teachers And 150 Parents Views Expressed In The Polls. The Analysis Of The Results Obtained, Agreed To The Verification Of The Assumptions, Scope Of The Objectives And To The Determination Of The Conclusions, Recommendations And Proposed. According To The Results Of The Surveys, Found That Aggressive Behavior Or Misconduct In Many Learners Is Generated (Or) By Conflicts Of Personality, Family Problems, There Is Rivalry Between Teammates, Selfishness, Superiority, Psychological Disorders As Fear, Anxiety, Low Self-Esteem, These Are Intrinsic Factors Affecting Behavior Of The Students At The United Educative San Carlos. In The Same Way There Are Extrinsic Factors, Generated By The External Environment, Such As The Environment Where Form And Develop Learners, School, Training Centers And Society. Analyzing The Above Context And The Needs Of The Educational Community, Was Defined As Proposal Preparation Of Lectures, Where Explaining The Regulatory Standards Of Ethics And Moral, Which Promote And Incite Students To Behave Well In And Out Of The Educational Institution. The Purpose Of The Proposal Is To Eliminate, Reduce And Control The Intrinsic And Extrinsic Factors That Affect The Performance Of Learners, Prioritizing Values, Education And Cultural Development.